(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the role of modern fitness sports in developing the professional-applied physical preparedness of cadets in military educational institutions. The pedagogical and physiological foundations of CrossFit, workout training, and resistance exercises are analyzed in the context of improving cadets’ endurance, strength, speed, agility, and psychological resilience. The study highlights the importance of integrating fitness-based training methods into military education as an effective means of enhancing combat readiness, physical performance, and professional competence. Particular attention is given to the application of functional training technologies that contribute to the comprehensive development of cadets’ physical and mental capabilities under conditions similar to real military activities.